Development of a Maluku Local Wisdom-Based Science E-Module to Enhance Elementary School Students’ Conceptual Mastery - Handrini Buton; Anasufi Banawi; Dinar Riaddin (Institute of Multidisciplinary Research and Community Service, 2026)
Science learning, particularly botany in elementary school, is often constrained by low mastery of concepts due to plant blindness. This research aims to develop, test its feasibility, and measure the effectiveness of the Rambuku E-Module (Maluku’s Cultural Diversity), based on local wisdom, to overcome these obstacles. This research and development (RD) study applied the ADDIE framework and integrates a pre-experimental one-group pretest-posttest design. The research participants comprised 3 expert validators, 2 science teachers, and 30 Grade IV students from Private Islamic Elementary School (MIS) Al-Madinah Ambon, who were selected through purposive sampling. Data collection used a Likert-scale questionnaire (1–4) to assess eligibility parameters and 20 multiple-choice objective test items to measure students' cognitive learning outcomes (C1–C4). The expert board's assessment recorded a very high validity score of 98% (Very Valid). The practicality parameter was also deemed very practical, with positive responses from teachers (92%) and students (92.42%). Inferential analysis using paired t-tests confirmed a highly significant increase in learning outcomes, with a group-average N-gain score of 0.77 (High). The integration of local content on cloves and nutmeg has proven effective as a cognitive bridge for contextualizing science material. The Rambuku E-Module has been validated as feasible and effective in improving children's understanding of science. This study recommends applying this model of digital culture-responsive development on a broader regional scale. Keywords: ADDIE, concept mastery, e-module, Maluku local wisdom, plant blindness.